Home Range and Ranging Behaviour of Bornean Elephant (Elephas maximus borneensis) Females - Raymond Alfred; Abd Hamid Ahmad; Junaidi Payne; Christy William; Laurentius Nayan Ambu; Phua, Mui How; Benoit Goossens (Public Library Science, 2012)
Background Home range is defined as the extent and location of the area covered annually by a wild animal in its natural habitat. Studies of African and Indian elephants in landscapes of largely open habitats have indicated that the sizes of the home range are determined not only by the food supplies and seasonal changes, but also by numerous other factors including availability of water sources, habitat loss and the existence of man-made barriers. The home range size for the Bornean elephant had never been investigated before.